Effects of Zanthoxylum bungeanum M. and Capsicum annuum L. oil on the formation of aroma characteristics of Jiao-ma chicken as evaluated by GC-MS and E-nose - WANG,Lixia (2022)
Abstract Spices have long been used in many countries to enhance or modify the flavor of meat and meat products. In general, different cooking treatments of spices can produce significantly different flavor. Jiao-ma chicken (JMC), as a traditional and characteristic cuisine in China, is prepared by boiled chicken seasoned with its exquisite flavor sauce. The delicious flavor of its sauce has won great popularity, and fried chili pepper (Capsicum annuum L.) oil (CPO) and pricklyash peel (Zanthoxylum bungeanum M.) oil (PPO) are its essential ingredients. To investigate the effects of CPO and PPO on the formation of aroma characteristics of JMC, the volatiles of CPO and PPO with and without chicken soup (CS) were analyzed by SPME/GC-MS. A total of 69 and 64 volatiles were identified in semi-finished JMC sauce (CS, CPO, and PPO) and final JMC sauce, respectively. GC-MS results showed that the composition and proportions of volatiles were significantly changed. Adding CPO and PPO to the basic CS generated several terpenes, and caused significant decreases in alcohols, aldehydes, and ketones, resulting in an exquisite spicy flavor of JMC sauce. Combined with GC-O and principal component analysis (PCA) results, it was found that 23 volatiles positively involved in the aroma formation, and might be significantly contributed to the unique flavor of JMC sauces.